TRANSPORMASI PEMBELAJARAN DIGITAL DALAM PENDIDIKAN DI SEKOLAH DASAR NEGERI 12 KOTO TINGGI KECAMATAN BASO - Erlinda, Rosni; Inge Angelia; Sudirman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
At this time education must be able to follow the development of technology and times, it’s run quickly. Education can prepare graduates with skills that the needs of the business world and the times. Education must be able to prepare graduates with high competitiveness. That’s why the educational institutions must use technology digital in lesson activities. The aims of the research is to know the transformation of digital learning in education at Elementary School Number 12 Koto Tinggi. The research method used is qualitative research with descriptive analysis and inductive analysis. The sample of this research is the teachers in Elementary School Number 12 Koto Tinggi. Data collection was done through interviews and observations. The research results indicate the impact of digital learning transformation in education at Elementary School Number 12 Koto Tinggi.